Triguna-Based Psychospiritual Rehabilitation for Victims: A Srimad Bhagavad Gita-Inspired Intervention - Kumkaria, Bodhraj; Tiwari, Himalaya (International Journal of Psychosocial Rehabilitation, 2020)
The present study investigated the impact of a six-week Bhagavad Gītā-based psychospiritual intervention on Triguna traits and psychological well-being among adult trauma victims in the Rajasthan (India). Grounded in Indian philosophical psychology, the intervention combined shloka contemplation, guided meditation, cognitive reframing, and affirmation journaling. A total of 20 participants (10 males, 10 females) were assessed pre- and post-intervention using the Vedic Personality Inventory (VPI) and Ryff’s 42-item Psychological Well-Being Scale (PWB). Pairedsample t-tests revealed statistically significant increases in Sattva (p < .001, d = 2.83) and significant decreases in Rajas (p < .001, d = –2.22) and Tamas (p < .001, d = – 2.00). Similarly, all six domains of psychological well-being showed significant improvements, with the strongest effects in Purpose in Life (p < .001, d = 2.95) and Self-Acceptance (p < .001, d = 2.09). The results suggest that the Gītā-based module serves as an effective psychospiritual rehabilitation tool by fostering inner clarity, emotional regulation, and positive identity reconstruction. This study contributes to the growing field of Indian indigenous psychology and offers an empirically supported intervention model for trauma recovery